2007
DOI: 10.3758/bf03196815
|View full text |Cite
|
Sign up to set email alerts
|

Impressions of force in visual perception of collision events: A test of the causal asymmetry hypothesis

Abstract: White, P. A. (2012). The experience of force: The role of haptic experience of forces in visual perception of object motion and interactions, mental simulation, and motion-related judgments. Psychological Bulletin, 138(4), 589-615.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
105
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(122 citation statements)
references
References 11 publications
15
105
2
Order By: Relevance
“…In simple cases like this one, the presence of motion itself is enough for the assignment of an agent or patient role to an object. For example, when participants are asked to describe such an event, they will typically say "One ball set the other one into motion," but very few will say "One ball stopped the other," suggesting that they naturally associate motion and agency 2 (White, 2007). In order to study the roles of motion and contact on moral judgments, we designed a simple setting that included three interacting objects-the Actor, Victim, and Harm-where the Actor's behavior led to the Victim contacting the Harm, and subsequently dying.…”
Section: The Physical Aspect Of Causality and Its Implications To Mormentioning
confidence: 99%
“…In simple cases like this one, the presence of motion itself is enough for the assignment of an agent or patient role to an object. For example, when participants are asked to describe such an event, they will typically say "One ball set the other one into motion," but very few will say "One ball stopped the other," suggesting that they naturally associate motion and agency 2 (White, 2007). In order to study the roles of motion and contact on moral judgments, we designed a simple setting that included three interacting objects-the Actor, Victim, and Harm-where the Actor's behavior led to the Victim contacting the Harm, and subsequently dying.…”
Section: The Physical Aspect Of Causality and Its Implications To Mormentioning
confidence: 99%
“…However, impressions of forces in visually perceived interactions do occur. The typical stimuli in the studies that have shown this are simple collision events in which a moving object contacts a stationary one, and the stationary one then moves off (White, 2007(White, , 2009a. White (2012) argued that these visual impressions of forces are derived from experiences of acting on objects.…”
Section: Actions On Objectsmentioning
confidence: 99%
“…This notion is supported by the fact that in not one of Michotte's (1963) experiments did participants suggest that object B stopped the movement of object A. Recent studies have found additional evidence for an asymmetrical interpretation of the direction of force in causal events (White, 2006(White, , 2007.…”
Section: Perspectives On the Origin Of The Ability To Perceive Causesmentioning
confidence: 92%
“…However, mounting evidence has demonstrated that top-down knowledge about objects influences the impression of causality produced by watching a collision (launching) event. Namely, it has been noted that an impression of force seems to accompany the impression of causality produced by a visual launching event (White, 2007(White, , 2009). …”
Section: Perspectives On the Origin Of The Ability To Perceive Causesmentioning
confidence: 99%
See 1 more Smart Citation